Mothers' Facebook posts about infant health: findings from the Grow2Gether study - Stacey Kallem; Rachel S. Gruver; Senbagam Virudachalam; Alexander G. Fiks (BMC, 2018)
Abstract Background Social media is a common way for mothers to seek advice about their infants. However, little is known about how low-income urban mothers use social media to obtain infant health information and whether this information is consistent with expert pediatric recommendations. Objectives (1) identify the types of health questions asked by low-income mothers of infants in a social media parenting group; (2) describe whether peer answers are consistent with or contradict AAP guidelines; (3) identify the practices that mothers post about that are inconsistent with AAP guidelines. Methods Forty-three low-income mothers were enrolled in Grow2Gether, a private Facebook group intervention focused on infant care and moderated by a psychologist. All health questions posted by mothers were coded thematically; answers to questions from the group were assessed for consistency with American Academy of Pediatrics (AAP) guidelines related to infant feeding, sleep, screen time, and safety. Additionally, all unique posts that contained practices inconsistent with these AAP guidelines were thematically coded. Results In total, 215 posts were coded. Participants posted 61 questions related to infant health, most commonly solid food introduction (8/61), teething (8/61), and breastfeeding (7/61). Of the 77 answers given by peers, 6 contradicted guidelines. Separately, mothers had 73 posts demonstrating practices inconsistent with AAP guidelines [safe sleep (43/73) and screen time (21/73)]. Conclusions Mothers' Facebook group interactions in the context of an infant care intervention revealed that when mothers posed direct questions regarding infant health, their peers generally gave answers that did not contradict AAP guidelines. In contrast, mothers' posts simply describing sleep and screen time practices commonly contradicted guidelines.